The harmonisation of rules on the recognition and enforcement of foreign judgments in the Southern African Customs Union - Rossouw, Mandi (University of the Western Cape, 2013)
The thesis considers the approaches followed by the European Union with the Brussels Regime, the federal system of the United States of America under the ‘full faith and credit clause’; the inter-state recognition scheme under the Australia and New Zealand Trans- Tasman judicial system; as well as the convention-approach of the Latin American States. It finds that the most suitable approach for the SACU is the negotiation and adoption by all SACU Member States of a multilateral convention on the recognition and enforcement of foreign judgments, comparable to the 1971 Convention of the Hague Conference on Private International Law; the EU Brussels I Regulation and the Latin-American Montevideo Convention, as complemented by the La Paz Convention. It is imperative that a proposed convention should not merely duplicate previous efforts, but should be drafted in the light of the legal, political and socio-economic characteristics of the SACU Member States. The current legislative provisions in force in SACU Member States are compared and analysed, and the comparison and analysis form the basis of a proposal for a future instrument on recognition and enforcement of foreign judgments for the region. A recommended draft text for a proposed Convention on the Recognition and Enforcement of Foreign Judgments for the SACU is included. This draft text could form the basis for future negotiations by SACU Member States
Keywords: Civil and commercial transactions; Cross-border litigation; Foreign judgments; International Trade; Recognition and enforcement; Regional integration; Trade facilitation